THE ROLE OF MANAGEMENT ACCOUNTING IN THE FORMATION OF PROFIT IN THE TRADE ORGANIZATIONS - O. Andreeva; O. Diakonova (Вестник университета)
Trade organizations in modern conditions of managing has significantly increased the role of profit. Search of reserves of increase in profit and profitability is possible only on the basis of analysis and economic justification of expenses and income. These categories are the main objects of management accounting in trade. The subject of research is the trade organization. The purpose of the study is to determine the influence of management accounting on the profit growth of the organization. The main scientific-practical result is the formation of control algorithm for profit trade organization. The methodological basis of the research was the views and conclusions formed in scientific works of domestic authors. The conclusions and recommendations presented in the paper, can be used at reading lectures and seminars in management accounting.